45,X Turner's syndrome in monozygotic twin sisters. - Pescia, G (1975)
A 7-year-old girl was admitted to the hospital for anaemia, secondary to intestinal blood los (melaena). She was found to have 45,X Turner's syndrome. Her identical twin sister also had Turner's syndrome with a 45,X chromosome complement. According to various criteria the probability of monozygosity was 0.9905. Although the incidence of twinning is greater than usual in families of patients with Turner's syndrome, affected cases have only been observed in twin sisters on six occasions. It seems therefore that the 45,X chromosome complement itself is not a factor predisposing to twinning, but that in some families, a factor is at play, which cuases either twinning or the 45,X aneuploidy, or both.